Introducing regular expressions : Javascript and typescript - Krause, Jörg, 1964- (For professionals by professionals, 2017)
This book is your easy-to-digest and concise guide to regular expressions in JavaScript, this book teaches you the very basics and can be used in the browser or on the server. Explore and understand how to use regular expressions in all JavaScript environments. Presented in four key concept sections, Introducing Regular Expressions shows how to create and use regular expressions to accelerate your JavaScript development. This book is for developers of web applications who want to explore the capabilities of JavaScript based apps on both, client and server. It's suitable for beginners that have a basic understanding of JavaScript already.